Experimental Investigation of Droplet Evaporation of Suspension Based on Water with Subsurface Admixtures in a Flame Area - Dmitrienko M. A. Margarita Aleksandrovna; Vysokomornaya O. V. Olga Valeryevna; Jean Claude Legros; Shcherbinina A. A. Anastasiya Anatolievna (2015, 2015)
Title screen